Berzosertib plus gemcitabine versus gemcitabine alone in platinum-resistant high-grade serous ovarian cancer: a multicentre, open-label, randomised, phase 2 trial. Issue 7 (July 2020) - Konstantinopoulos, Panagiotis A; Cheng, Su-Chun; Wahner Hendrickson, Andrea E; Penson, Richard T; Schumer, Susan T; Doyle, L Austin; Lee, Elizabeth K; Kohn, Elise C; Duska, Linda R; Crispens, Marta A; Olawaiye, Alexander B; Winer, Ira S; et al.
Summary: Background: High-grade serous ovarian cancers show increased replication stress, rendering cells vulnerable to ATR inhibition because of near universal loss of the G1/S checkpoint (through deleterious TP53 mutations), premature S phase entry (due to CCNE1 amplification, RB1 loss, or CDKN2A mRNA downregulation), alterations of homologous recombination repair genes, and expression of oncogenic drivers (through MYC amplification and other mechanisms). We hypothesised that the combination of the selective ATR inhibitor, berzosertib, and gemcitabine could show acceptable toxicity and superior efficacy to gemcitabine alone in high-grade serous ovarian cancer. Methods: In this multicentre, open-label, randomised, phase 2 study, 11 different centres in the US Experimental Therapeutics Clinical Trials Network enrolled women (aged ≥18 years) with recurrent, platinum-resistant high-grade serous ovarian cancer (determined histologically) and Eastern Cooperative Oncology Group performance status of 0 or 1, who had unlimited previous lines of cytotoxic therapy in the platinum-sensitive setting but no more than one line of cytotoxic therapy in the platinum-resistant setting. Eligible patients were randomly assigned (1:1) to receive intravenous gemcitabine (1000 mg/m 2 ) on day 1 and day 8, or gemcitabine plus intravenous berzosertib (210 mg/m 2 ) on day 2 and day 9 of a 21-day cycle until disease progression or intolerable toxicity. Randomisation was done centrally using the Theradex Interactive Web Response System, stratified by platinum-free interval, and with a permuted block size of six. Following central randomisation, patients and investigators were not masked to treatment assignment. The primary endpoint was investigator-assessed progression-free survival, and analyses included all patients who received at least one dose of the study drugs. The study is registered with ClinicalTrials.gov, NCT02595892, and is active but closed to enrolment. Findings: Between Feb 14, 2017, and Sept 7, 2018, 88 patients were assessed for eligibility, of whom 70 were randomly assigned to treatment with gemcitabine alone (36 patients) or gemcitabine plus berzosertib (34 patients). At the data cutoff date (Feb 21, 2020), the median follow-up was 53·2 weeks (25·6–81·8) in the gemcitabine plus berzosertib group and 43·0 weeks (IQR 23·2–69·1) in the gemcitabine alone group. Median progression-free survival was 22·9 weeks (17·9–72·0) for gemcitabine plus berzosertib and 14·7 weeks (90% CI 9·7–36·7) for gemcitabine alone (hazard ratio 0·57, 90% CI 0·33–0·98; one-sided log-rank test p=0·044). The most common treatment-related grade 3 or 4 adverse events were decreased neutrophil count (14 [39%] of 36 patients in the gemcitabine alone group vs 16 [47%] of 34 patients in the gemcitabine plus berzosertib group) and decreased platelet count (two [6%] vs eight [24%]). Serious adverse events were observed in ten (28%) patients in the gemcitabine alone group and nine (26%) patients in the gemcitabine plus berzosertib group. There was one treatment-related death in the gemcitabine alone group due to sepsis and one treatment-related death in the gemcitabine plus berzosertib group due to pneumonitis. Interpretation: To our knowledge, this is the first randomised study of an ATR inhibitor in any tumour type. This study shows a benefit of adding berzosertib to gemcitabine in platinum-resistant high-grade serous ovarian cancer. This combination warrants further investigation in this setting. Funding: US National Cancer Institute.